Defect Engineering Strategies for Nitrogen Reduction Reactions under Ambient Conditions. Issue 6 (24th October 2018) - Yan, Dafeng; Li, Hao; Chen, Chen; Zou, Yuqin; Wang, Shuangyin
Abstract: The production of ammonia from N2 molecules under ambient conditions [electro (photo) chemical reduction] is one of the most attractive topics in the energy‐related field due to its unique advantages and great potentials. Recently, various catalysts have been explored to show certain activities in nitrogen reduction reactions (NRRs) at room temperature and atmospheric pressure. To further improve the catalytic activity and increase the selectivity, the catalysts should be rationally designed to introduce extra active sites for the N2 molecule adsorption and activation. This review summarizes recent progress of the defect engineering strategies to design highly efficient electrochemical or photocatalytic NRR nanocatalysts. The defect sites would serve as the active center for the NRR and further enhance its intrinsic performance. The defect engineering strategies are summarized in different categories, including vacancies (oxygen, nitrogen, and sulfur vacancies), doping (metal doping and nonmetal doping), amorphous phases (amorphous noble metal and amorphous transition metal), size effects, and structure effects. In addition, the different ammonia determination methods are summarized and compared in order to obtain more credible and veritable NRR performance results. Abstract : This review focuses on the defect engineering strategies to design highly efficient electrochemical or photocatalytic nitrogen reduction reaction (NRR) nanocatalysts. The defect sites would serve as the active sites for NRR and further enhance its intrinsic performance. The defect engineering strategies are summarized in different categories, including vacancies, doping, amorphous phases, size effect, and structure effect.